A Theory of Intergenerational Mobility - Becker, Gary S.; Kominers, Scott Duke; Murphy, Kevin M.; Spenkuch, Jörg L. (Journal of Political Economy, 2018)
We study the link between market forces, cross-sectional inequality, and intergenerational mobility. Emphasizing complementarities in the production of human capital, we show that wealthy parents invest, on average, more in their offspring than poorer ones. As a result, economic status persists across generations even in a world with perfect capital markets and without differences in innate ability. In fact, under certain conditions, successive generations of the same family may cease to regress toward the mean. We also consider how short- and long-run mobility are affected by changes in the returns to human capital.